Transfection of the BDNF Gene in the Surviving Dopamine Neurons in Conjunction with Continuous Administration of Pramipexole Restores Normal Motor Behavior in a Bilateral Rat Model of Parkinson’s Disease - Alina Benítez-Castañeda; Verónica Anaya-Martínez; Armando de Jesús Espadas-Alvarez; Ana Luisa Gutierrez-Váldez; Luis Fernando Razgado-Hernández; Patricia Emmanuelle Reyna-Velazquez; Liz Quintero-Macias; Daniel Martínez-Fong; Benjamín Florán-Garduño; Jorge Aceves (Parkinson's Disease, 2024)
In Parkinson’s disease (PD), progressive degeneration of nigrostriatal innervation leads to atrophy and loss of dendritic spines of striatal medium spiny neurons (MSNs). The loss disrupts corticostriatal transmission, impairs motor behavior, and produces nonmotor symptoms. Nigral neurons express brain-derived neurotropic factor (BDNF) and dopamine D3 receptors, both protecting the dopamine neurons and the spines of MSNs. To restore motor and nonmotor symptoms to normality, we assessed a combined therapy in a bilateral rat Parkinson’s model, with only 30% of surviving neurons. The preferential D3 agonist pramipexole (PPX) was infused for four ½ months via mini-osmotic pumps and one month after PPX initiation; the BDNF-gene was transfected into the surviving nigral cells using the nonviral transfection NTS-polyplex vector. Overexpression of the BDNF-gene associated with continuous PPX infusion restored motor coordination, balance, normal gait, and working memory. Recovery was also related to the restoration of the average number of dendritic spines of the striatal projection neurons and the number of TH-positive neurons of the substantia nigra and ventral tegmental area. These positive results could pave the way for further clinical research into this promising therapy.